Impact of climate change on public health in Brazil - Mariana Abou Mourad Ferreira; Yuri Luiz Reis Leite; Crispim Cerutti Junior; Creuza Rachel Vicente (Wiley, 2023)
Abstract Brazil is South America's largest country and economy, represented mainly by agricultural commodities. Its vast rainforest and biodiversity are at constant risk from human actions that are seen by scientists contributing to climate change. This article dissects how Brazil influences and is directly and indirectly affected by climate change and possible strategies to control the current situation. Climate change impacts Brazilian public health in multi‐scenarios and is influenced by socioeconomical and geopolitical aspects, such as urbanization, access to sanitation and sewage, precipitation intensity and frequency, and public health policies. Therefore, surveillance and control measures, alongside socioeconomic policies, must be orchestrated to minimize human actions that impact climate change.